Pengaruh Kepemimpinan, Tuntutan Tugas dan Karier Staknan terhadap Stres Kerja, dan Dampaknya bagi Komitmen Organisasi dan Organization Citizienship Behavior Karyawan PT Alfa Retailindo Surabaya - Pandyi Soegiono (Jurnal Aplikasi Manajemen, 2010)
Target of this research is to analyse influence of leadership, demand, career of stagnant to duty stress, influence of duty stress to organizational commitment and influence of organizational commitment to OCB employees.Variable which used in this research is Leadership, Demand Duty, Career of stagnant n, Stress, Organizational commitment and Organizational Citizienship Behavior. With object research of PT. Alpha of Retailindo, Tbk. Measurement of variable use international scale with measurement method use scale of likert, with amount of sample 100 people. Model used to analyse data in this research is Structural Equation Modelling (SEM)Conclusion of research which have been conducted to know influence of Factor negativity and significant of Leadership to Factor of Job unprovable Stress is its truth and influence of significant and is positive of Factor of Job Demand to Factor of Job proven Stress is its truth, and also influence of significant and is positive of Career Stagnation to Factor of Job unprovable Stress is its truth and influence of Factor negativity and significant of Job Stress to Factor of Organizational unprovable Commitment its truth. While influence of significant and is positive of Factor of Organizational Commitment to Factor of OCB at PT. Alpha of Retailindo Surabaya tried and true.Keywords: leadership, duty demand, career of stagnant, job strees, organizational comitment and behavior citizienship organizational